New sauropod tracks from the Yacoraite Formation (Maastrichtian–Danian), Valle del Tonco tracksite, Salta, northwestern Argentina - Díaz Martínez, Ignacio (2017)
Fil: Díaz Martínez, Ignacio. Universidad Nacional de Rio Negro. Instituto de Investigaciones en Paleobiologia y Geologia. Río Negro, Argentina.